Logistika v kmetijstvu - Lisec, Andrej (University of Maribor Press, 2022)
Logistics in Agriculture. The book deals with logistics in agriculture, which includes chapters on logistics related to agriculture, history in this field, food production, self-sufficiency in connection with the distribution of locally produced food, mechanization, transport of food in controlled temperature conditions, crop labeling, agricultural waste and a view of agriculture in the future, including the use of drones.